Understanding eating disorders - Gilles, Renae (21st century skills library. Upfront health., 2020)
Explores the dangerous health detriments of eating disorders, discussing how social and emotional issues and mental illness can cause people, especially adolescents, to develop an unhealthy relationship with food. Offers advice on making healthy choices and seeking help. Includes photographs, sidebars, a glossary, an index, and resources for further research.